A man inside a machine: Commodification, the political unconscious, and the antihuman attitude in RoboCop. (1st February 2022) - Parr, Christopher
Abstract : This article traces the manifestation of the antihuman attitude in twenty-first century sf cinema, particularly in the cyborg film. The antihuman attitude is most clearly recognizable in apocalyptic and post-apocalyptic cinema, where it provides spectacular images of humanity's destruction. However, it also finds a much subtler visualization in films featuring technologically augmented characters. While presenting narratives which ultimately reinstate a privileged Enlightenment humanism, the visual economy of these films continues to represent its protagonists as dehumanized commodities. Engaging with Fredric Jameson's political unconscious and film genre theory, the article explores how the antihuman attitude manifests in 2014's RoboCop through visuals which undermine the autonomy of its human protagonist and contradict the film's humanist narrative.